A Single Intracoronary Injection of Midkine Reduces Ischemia/Reperfusion Injury in Swine Hearts: A Novel Therapeutic Approach for Acute Coronary Syndrome - Ishiguro, Hisaaki; Horiba, Mitsuru; Takenaka, Hiroharu; Sumida, Arihiro; Opthof, Tobias; Ishiguro, Yuko S.; Kadomatsu, Kenji; Murohara, Toyoaki; Kodama, Itsuo (Frontiers in Physiology, 2011)
Several growth factors are effective for salvaging myocardium and limiting infarct size in experimental studies with small animals. Their benefit in large animals and feasibility in clinical practice remains to be elucidated. We investigate the cardioprotective effect of midkine (MK) in swine subjected to ischemia/reperfusion (I/R). I/R was created in swine by left anterior descending coronary artery occlusion for 45 min using a percutaneous over-the-wire balloon catheter. MK protein was injected as a bolus through the catheter at the initiation of reperfusion (midkine injected group; MKT). Saline was injected in controls (CONT). Survival rate 24h after I/R was significantly higher in MKT than in CONT, whereas infarct size/area at risk was almost 5 times smaller. Echocardiography in MKT revealed a significantly higher percent wall thickening of the interventricular septum, a higher % fractional shortening and a lower E/e’ compared with CONT. LV catheterization in MKT showed a lower LVEDP, and a higher dP/dtmax compared with CONT. TUNEL-positive myocytes and CD45-positive cell infiltration in the peri-infarct area were significantly less in MKT than in CONT. Here, we showed that a single intracoronary injection of MK protein in swine hearts at the onset of reperfusion dramatically reduces infarct size and mortality and ameliorates systolic/diastolic LV function. This beneficial effect is associated with a reduction of apoptotic and inflammatory reactions. MK application during percutaneous coronary intervention may become a promising adjunctive therapy in acute coronary syndromes.